FAKTOR YANG MEMPENGARUHI LOYALITAS NASABAH BANK SYARIAH MANDIRI KC BANYUWANGI - Miko Andi Wardana (Forum Manajemen STIMI Handayani Denpasar, 2021)
Departing from the main issue that is being discussed in many societies related to Islamic banking, which is a byword in today's society. Therefore, the initiative of the researcher to raise this problem is the subject of the title of this study. And this study aims to determine the effect of Islamic banking services and products on customer loyalty in taking funding and financing at PT Bank Syariah Mandiri Banyuwangi Branch. The research method uses multiple linear regression which is sourced from primary data of respondents. Data was collected by filling out questionnaires for 70 customers of PT Bank Syariah Mandiri Banyuwangi Branch. The sampling technique uses the Cluster Random Sampling technique, because the number of sample populations cannot be known accurately, which allows for no design related to the sampling frame, and the presence of the population is randomly distributed or collected in different spheres. at PT Bank Syariah Mandiri Banyuwangi Branch were respondents. Data analysis using SPSS 25 for windows. The results of this study indicate that the service variable does not have a significant effect on customer loyalty at PT Bank Syariah Mandiri Banyuwangi Branch, so that the hypothesis is accepted. Service has no influence on customer loyalty. Product variables have a significant effect on Customer Loyalty variables. Product variable (X2) has an effect on the Customer Loyalty variable (Y). Service variable (X1) and the Product variable (X2) simultaneously or simultaneously have an influence on the Customer Loyalty variable (Y).